Packaging House of Cards and The Knick: How talent intermediaries manage the indie-auteur brand to sell premium television. (June 2020) - Stubbs, Andrew
The article explores the migration of indie-auteurs to television during the 2010s. Using David Fincher and Steven Soderbergh's work on House of Cards and The Knick as case studies, the article argues that talent intermediaries such as producers and talent managers have sought to mobilize the indie-auteur, a branded identity and authorial discourse, to package premium television programmes to exploit growing competition between channels and platforms. The article also explores repercussions of the indie-auteur's insertion in television as a mark of distinction, arguing that it becomes increasingly important to be aware of the systems behind it.